2018
DOI: 10.1111/ggi.13494
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and physical factors predisposing middle‐aged and older Japanese adults to falls and fall‐related fractures in the home

Abstract: Environmental factors, such as living in a barrier home, are critical for fall-related fractures, in addition to demographic and physical factors. A multidisciplinary approach that considers both physical and environmental factors is necessary for reducing the incidence of fall-related fractures among middle-aged and older Japanese adults. Geriatr Gerontol Int 2018; 18: 1372-1377.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Moreover, other important barriers are problems with access to transport and difficulties with access to health facilities [35]. Architectural barriers occurring at home are a frequent cause of falls and fractures; thus, they also increase fears of falling, thus limiting the activity of older people [36]. Consequently, barriers limit the activity of older people both at home and outside the home [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other important barriers are problems with access to transport and difficulties with access to health facilities [35]. Architectural barriers occurring at home are a frequent cause of falls and fractures; thus, they also increase fears of falling, thus limiting the activity of older people [36]. Consequently, barriers limit the activity of older people both at home and outside the home [37].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that an effective modification of the home environment reduces the risk of falls 16) . Furthermore, in their cross-sectional survey among community-dwelling adults in Japan, Tanaka et al reported that living in a barrier home was a risk factor for falls 17) . Third, we did not survey the details of prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
“…The group consisted of four physical therapists: two of them work in academic fields related to community-based rehabilitation and geriatrics and are actively committed to research and teaching about fall prevention and management, and the other two have expertise in community-based rehabilitation work in a clinical setting and are engaged in assistive devices and home modifications. Possible items for the tool were listed based on a narrative review of scientific articles, 7,12,13,[15][16][17][18] existing instruments and guidelines. 19,20 Environmental hazards in each category were chosen from the list while considering Japanese housing structure.…”
Section: Assessment Of Environmental Hazardsmentioning
confidence: 99%
“…Traditional Japanese houses, for example, have several unique structures, such as the Agari‐kamachi at the entrance – which is a boundary between the outside of a house, where people walk with shoes on, and the inside, where people put slippers on. Only a few studies have examined the association of environmental hazards with falls in older people in Japan 12,13 …”
Section: Introductionmentioning
confidence: 99%